Reformulation of Judicial Principles in Judicial Review Cases Based on Open Legal Policy by the Constitutional Court - Teja Aulia; Nanang Sri Darmadi (Rule of Law Studies Journal, 2026)
Background:In Indonesia's constitutional system, the Constitutional Court has the authority to review laws against the 1945 Constitution to ensure constitutional supremacy and protect citizens' constitutional rights. In practice, the Constitutional Court not only acts as a negative legislature, invalidating legal norms, but also, in some decisions, acts as a positive legislature through the application of the principle of judicial activism. However, the application of this principle often generates debate, particularly when it relates to norms of an open legal policy nature, which are essentially within the authority of the lawmakers. Aims:This study aims to analyze the application of the principle of judicial activism by the Constitutional Court in cases of judicial review of laws related to the norm of open legal policy, and to examine the consistency of its application in constitutional judicial practice in Indonesia. Methods:This study employs a juridical-normative research method with a case approach, a conceptual approach, and a comparative approach. Data were obtained through a literature review, encompassing primary legal materials in the form of legislation and Constitutional Court decisions, as well as secondary legal materials in the form of academic literature and legal doctrine. Data analysis was conducted qualitatively through a content analysis of Constitutional Court decisions related to the application of the principle of judicial activism. Result:The research results show that the Constitutional Court has applied the principle of judicial activism in several of its decisions by formulating or adding new legal norms during the judicial review process. However, this principle has not been consistently applied, particularly in cases related to open legal policy norms. In some decisions, the Constitutional Court has refused to review these norms, arguing that this falls within the authority of the legislators, while in other decisions, the Constitutional Court has intervened in norms that constitute open legal policy. Conclusion:This study concludes that the Constitutional Court's application of the principle of judicial activism still requires clearer parameters to avoid inconsistencies in its judicial review practices. Such clarity is crucial for maintaining a balance of power between the judiciary and the legislature and strengthening the Constitutional Court's role as a guardian of the constitution in a democratic state governed by the rule of law.